Structural, morphological and electrochemical characterization of the degradation processes during the oxygen reduction reaction of iron(II) phthalocyanine supported on carbon nanotubes. (1st April 2023) - Kinkelin, Simon-Johannes; Steimecke, Matthias; Dieterich, Emil; Bron, Michael
Abstract: A non-noble metal catalyst (Fe-Nx @MWCNTs), which was prepared by wet impregnation of surface-functionalized multi-walled carbon nanotubes (MWCNTs) with iron(II) phthalocyanine (FePc) and heat treatment, as well as the functionalized MWCNTs without FePc were examined towards their performance for the oxygen reduction reaction (ORR) in neutral media and their structural properties during electrochemically forced degradation. Electroanalytical methods as well as in situ -Raman microscopy and ex situ -X-ray photoelectron spectroscopy (XPS) were applied at different levels of a two-stage accelerated stress test (AST). In particular, the comparability between the electrochemical, the in situ -Raman and the ex situ -XPS setup was confirmed. It was found that the iron central atom was leached out of the Fe-Nx -complex during the first stage of the AST causing a decline of ORR activity, still higher than that of the MWCNT support, which remained unaffected. During the second stage, the samples were subjected to stronger electrochemical stress by cycling to highly positive potentials, causing the formation of surface groups and an increase of double layer capacitance. The high potentials also destroy remaining catalytic NC moieties and the ORR activity of the catalyst approaches that of the bare support. With ongoing AST cycling, the overall current of the samples is heavily reduced which is attributed to loss of electric conductivity of the sample backbone by further oxidation. Graphical abstract: Image, graphical abstract